Improvement of okra (Abelmoschus esculentus) growth, yield and qualtiy by using plant growth regulators in vivo and in vitro conditions / Mekhled Mutiran Alenazi - Alenazi, Mekhled Mutiran (2011)
Studies were conducted to investigate the effects of plant growth regulators on okra growth, yield and quality development using different techniques of application in a commercial vegetable field in Banting, Selangor, Malaysia. The experimental design employed on the commercial field was a randomized complete block design (RCBD). The different growth hormones were applied directly, internally, to the selected parts of the okra plant. In the flower injection treatment, injection was applied on the okra flower using IAA at different concentrations. The pod set percentage, and length was maximal in the 25 mg/l IAA treatment compared to the control. Higher percentage of healthy seed per plant was also recorded using 25 mg/l IAA followed by control and 50 mg/l IAA. However, a high concentration of IAA (200 mg/l) inhibited seed production and brought about Stenospermocarpy which resulted in 100% aborted seeds. Total soluble solids (TSS) and vitamin C content in the pod markedly increased as a result of IAA application at all the different concentrations. The highest K+ content was found in 25 mg/l IAA treated plants. In addition, the iron (Fe) content increased significantly in IAA treatments at all concentrations compared to the control.